2016
DOI: 10.1017/s1092852916000444
|View full text |Cite
|
Sign up to set email alerts
|

Once-monthly paliperidone palmitate compared with conventional and atypical daily oral antipsychotic treatment in patients with schizophrenia

Abstract: Objective. This analysis of the Paliperidone Palmitate Research in Demonstrating Effectiveness (PRIDE) study (NCT01157351) compared outcomes after administration of once-monthly paliperidone palmitate (PP) vs conventional oral antipsychotics (COAs) or atypical oral antipsychotics (AOAs).Methods. PRIDE was a 15-month study of 444 individuals with schizophrenia and a history of incarceration. They were randomly assigned to PP or to 1 of 7 commonly prescribed OAs. Primary endpoint was time to first treatment fail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 32 publications
0
9
1
Order By: Relevance
“…A comparison between patients treated with PP1M and patients treated with FGA also showed small differences in the rate of premature discontinuation. In the PP1M group, the most frequent cause of dropout was loss to follow‐up …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…A comparison between patients treated with PP1M and patients treated with FGA also showed small differences in the rate of premature discontinuation. In the PP1M group, the most frequent cause of dropout was loss to follow‐up …”
Section: Resultsmentioning
confidence: 99%
“…The most significant finding emerging from the reviewed studies on PP1M was that the drug showed lower (or, at best, similar) dropout rates in all but one head‐to‐head comparison with several comparators, such as RIS‐LAI, FGA‐LAI, and both FGA and SGA in oral formulation …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, from a pharmacokinetic point of view, after a single dosage of a LAI formulation, relapse prevention derived for antipsychotic plasma levels enough to block up to 60% D2 receptors remains active for several weeks (up to 24 weeks if we use paliperidone LAI monthly). 41,42 All patients were closely monitored by multidisciplinary clinical staff to detect the presence of risk signs or complications (psychiatry, obstetricgynecology, endocrinology, and rheumatology).…”
Section: Discussionmentioning
confidence: 99%